Expression of aminopeptidase-n (CD 13) in normal tissues and malignant neoplasms of epithelial and lymphoid origin. Issue 1 (January 1994) - Dixon, J; Kaklamanis, L; Turley, H; Hickson, I D; Leek, R D; Harris, A L; Gatter, K C
Abstract : AIMS–To provide a detailed knowledge of the distribution of the CD13 molecule, also known as the protease aminopeptidase-N, on both normal tissues and malignant neoplasms of epithelial and lymphoid origin. METHODS–CD13 antigen was examined by immunocytochemistry, using a recently produced antibody (VS5E) alongside a commercially available anti-CD13 monoclonal antibody. The VS5E recognising CD13 was produced by immunising a doxorubicin resistant breast cancer cell line (MCF-7-ADr). A striking feature of this antibody was that it stained the doxorubicin resistant cells but not the parental cell line. Both antibodies were tested on a broad range of normal tissues and three common types of epithelial malignancy (colon n = 28, lung n = 30, breast n = 35), and 12 cases of Hodgkin's and 52 of non-Hodgkin's lymphomas. RESULTS–CD13 was expressed on many tissue and cell types outside the haematopoietic system. In particular it was present on breast epithelium and in 20% (seven of 35) of breast carcinomas, but absent in normal and neoplastic colonic and bronchial tissues and lymphomas. CONCLUSIONS–This study provides not only detailed information about the expression of the CD13 antigen, but also raises the important possibility that CD13 expression may correlate with drug resistance in breast carcinomas.